Diagnostics and Treatment of Peptic Ulcer in Adults (Clinical Guidelines of the Russian Gastroenterological Association, the Russian Society of Colorectal Surgeons, the Russian Endoscopic Society and the Scientific Society for the Clinical Study of Human Microbiome) - V. Т. Ivashkin; I. V. Mayev; Р. V. Tsarkov; М. Р. Korolev; D. N. Andreev; Е. К. Baranskaya; D. S. Bordin; S. G. Burkov; А. А. Derinov; S. К. Efetov; Т. L. Lapina; Р. V. Pavlov; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. The guidelines set out the modern methods of diagnostics and treatment of peptic ulcer and are created for gastroenterologists, primary care physicians, general practitioners, surgeons, endoscopists.Key points. The clinical guidelines contain modern views on the etiology and pathogenesis of peptic ulcer, its clinical features, methods of laboratory and instrumental diagnostics, the main approaches to conservative and surgical treatment. They include the criteria for assessment of the quality of medical care, the algorithm of the doctor's actions, as well as information for the patient.Conclusion. Knowledge of modern methods of diagnostics and therapy of peptic ulcers will contribute to improving the results of its treatment.